Incidence, Prevalence, and Trends in Endometriosis Diagnosis: A United States Population-Based Study From 2006 to 2015. Issue 11 (November 2021) - Christ, Jacob P.; Yu, Onchee; Schulze-Rath, Renate; Grafton, Jane; Hansen, Kelly; Reed, Susan D.
Abstract : (Abstracted from Am J Obstet Gynecol 2021; doi: 10.1016/j.ajog.2021.06.067). Endometriosis, defined as the presence of extrauterine endometrial tissue, often has serious symptoms that significantly impact the lives of those affected and is associated with annual health care costs of approximately 16, 500. Despite the significant societal and individual burden of endometriosis, prevalence and incidence data in the United States are lacking with prevalence rates ranging from 0.8% to 11% and incidence ranging from 4.2 to 35 per 10, 000 women-years.